The Political Economy of East Asia: striving for wealth and power - Leite, Alexandre Cesar Cunha (Meridiano 47 - Journal of Global Studies, 2017)
Resenha do livro: WAN, Ming. The Political Economy of East Asia: striving for wealth and power. Washington-DC: Congressional Quarterly Press, 2008. ISBN 978-1-933116-01-4.